IMPLICATION OF CONFLICT OF OWNERSHIP REGIONAL ASSETS IN THE EXPANSION OF BAU-BAU CITY IN THE TERRITORY OF EX BUTON SULTANATE - Darmin Tuwu (Jurnal Sosiologi Reflektif, 2017)
The article entitled "The Conflict of Ownership Regional Asset Between  Government of Buton Regency and Government of Bau-Bau Municipal " is part of my thesis in the Department of Sociology Faculty of Political and Social Sciences Gadjah Mada University. The conflict of two regional governments began when Kotif Bau-Bau was upgraded to Bau Bau City, where almost all of district's assets Buton regency's (premier) are within in the Bau-Bau City as the New Autonomous Region. This research apply qualitative approach using case study aiming to elaborate the context of the conflicts regional asset and their implications on both local governments, Buton Regency and Bau-Bau City. The results showed that the context of the conflict of ownership of regional assets was triggered by the difference of opinion on the contents of Law Number 13 Year 2001 related to the control of regional asset that is in the area of Bau-Bau City as the New Autonomous Region. The is no conclusive solution to the conflict that began in 2001, The effects of such conflicts are apparent in public services, Local Original Income, and social segregation.Konflik antara dua pemerintahan daerah ini, berawal ketika Kotif Bau-Bau ditingkatkan statusnya menjadi Kota Bau Bau, di mana hampir seluruh aset daerah kabupaten Buton (kabupaten induk) berada dalam wilayah Kota Bau-Bau selaku Daerah Otonomi Baru. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan studi kasus yang bertujuan untuk menguraikankonteks konflik aset daerah dan implikasinya terhadap kedua pemerintah daerah, Kabupaten Buton dan Kota Bau-Bau. Hasil penelitian menunjukkan bahwa konteks konflik kepemilikan aset daerah dipicu oleh perbedaan pendapat atas isi Undang-Undang Nomor 13 Tahun 2001 terkait penguasaan aset daerah yang berada di wilayah Kota Bau-Bau sebagai Kota Baru, Daerah Otonom Baru. Tidak ada solusi konklusif untuk konflik yang dimulai pada tahun 2001, Dampak dari konflik tersebut terlihat pada layanan publik, Pendapatan Asli Daerah, dan pemisahan sosial.Keywords: Conflict, Asset, Autonomy and Bau-Bau City